Multiple congenital encephalic malformations in a calf - Silva, Lorena F.; Rabelo, Rogério E.; Santos, Guilherme P.; Aguiar, Oton L. R.; Sonne, Luciana; Barros, Claudio S. L.; Sant’Ana, Fabiano J. F. de (Brazilian Journal of Veterinary Pathology, 2016)
Multiple congenital malformations of the central nervous system are uncommonly described in domestic animals. A 7-days-old, female, Holstein calf was submitted for necropsy with a history of opisthotonus and permanent lateral recumbence. Clinical signs included apathy, abdominal breathing, occasional flexion of the forelimbs, and decreasing of the superficial and deep sensibility in all limbs. Necropsy and histopathology revealed cerebellar hypoplasia, stenosis of the mesencephalic aqueduct, fusion of the rostral and caudal colliculi, secondary hydrocephaly, villous hypertrophy of the choroid plexus and heterotopy of cerebellar cellular components. Immunohistochemical labeling for the antibody anti-BVDV in fragments of brain resulted negative, suggesting that this virus did not participate in the pathogenesis of these malformations.